The importance of a good relationship between patient/dentist based on the obtaining of an informed consenr to prevent lawsuits - dos Santos, Karina Tonini; Garbin, Cléa Adas Saliba [UNESP]; Pacheco Filho, Antonio Carlos (My University, 2011)
The increased number of law suits in the Dentistry field constitutes an international trend. Patients well informed by the media and supported by the law sue their dentists, when they judge they were victim of bad practice. Professionals even with all discussion about this subject do not have the habit of prevent themselves. It is known that for a defensive practice the best way to avoid litigation is a good relationship with patient, based on dialog and on informed consent. This relation is very important, since patients who rely on their dentists rarely take them to justice. Hence, this article discusses the importance of this relation, as well as the obtaining of informed consent in order to prevent lawsuits.
Keywords: Lawsuit; Dentistry; Informed consent